Consideraciones jurídicas sobre la naturaleza en el contexto del bicentenario patrio: una indagación constitucional (Perú 1821 - 2021) - Foy Valencia, Pierre (2022)
This essay examines some legal premises on the notion of nature, based on a characterization of the constitutional legal system in the period 1821 -2021. A presentation of the motivation for this essay is followed by a brief retrospective view of nature from the legal standpoint through a diachronic approach to “constitutional regulated law” and nature. Some annotations are included about the legal system and nature at present to conclude with a brief forward looking appreciation of the issue.